(untitled) (International Journal of Environmental Sciences, 2025)
Background: Transformational leaders foster trust, encourage innovation, and provide individualized support, which is particularly impactful in high-stress professions like nursing. The study aims to explore the influence of transformational leadership on organizational commitment, psychological empowerment and well-being. Materials & Methods: A descriptive cross-sectional design was used with 289 staff nurses selected through consecutive sampling technique at selected hospitals, in Chennai. The tools uses were background variables proforma, global transformational leadership scale, rating scale on organizational commitment, psychological empowerment and on psychological Wellbeing. Results: The study revealed that most staff nurses were aged 20-35 years (92.4%), predominantly female (84.9%), with less than five years of experience (70.0%), and nearly half working in wards and OPD (42.8%). The mean scores (±SD) for transformational leadership, organizational commitment, psychological empowerment, and psychological well-being were 26.22/35 ± 5.16, 21.80/40 ± 5.25, 59.88/84 ± 18.66, and 42.42/56 ± 13.05, respectively. A strong positive correlation was found between psychological empowerment and well-being, while organizational commitment showed a weak positive correlation with empowerment. Transformational leadership significantly influenced psychological well-being, improving it by 12.6% after controlling for psychological empowerment (P < 0.001). The findings underscore the importance of demographic and work-related variables in shaping leadership, commitment, empowerment, and well-being among staff nurses. Conclusion: These findings underscore the importance of transformational leadership as a key factor in fostering positive outcomes for nurses, emphasizing its role in improving empowerment and well-being.